El uso de instrumentos científicos en los primeros vuelos aerostáticos tripulados - Molina García, Juan Alberto (ENDOXA, 2004)
After the Montgolfier’s invention of a hot-air balloon at the end of the 18th century, the success of the first manned-flight in an hydrogen balloon by the french physicist Charles on Ist december 1783, supposed the begining of a series of experiences on board of such aerial devices that would lead to a progresive knowledge of the behaviour of the upper atmosphere and to determine the variation of some properties of the air in relation with height. The purpose of this paper is to examine how the use of scientific instruments was decisive to obtain these results, so that it will be analised the work realised by some French balloonists in their rides; in a second part, it will be commented the work developed in Spain, to compare with the formerly mentioned.